4+-6+9=x

Simple and best practice solution for 4+-6+9=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4+-6+9=x equation:


Simplifying
4 + -6 + 9 = x

Combine like terms: 4 + -6 = -2
-2 + 9 = x

Combine like terms: -2 + 9 = 7
7 = x

Solving
7 = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
7 + -1x = x + -1x

Combine like terms: x + -1x = 0
7 + -1x = 0

Add '-7' to each side of the equation.
7 + -7 + -1x = 0 + -7

Combine like terms: 7 + -7 = 0
0 + -1x = 0 + -7
-1x = 0 + -7

Combine like terms: 0 + -7 = -7
-1x = -7

Divide each side by '-1'.
x = 7

Simplifying
x = 7

See similar equations:

| .10x+12y=2990 | | a/4-b/3=5/12 | | -2+5n+3n^2=0 | | 10=30/z | | 9p-19=5(p-2)-2(7-2p) | | 5v-5v+v=16 | | Y=-4(6)-10 | | (14-2x)+40=180 | | -2x-10=-2x-10 | | x-10y=13 | | 1=k/10-1 | | x^2-14x-40= | | (14-2x)+40=90 | | 12x+6y= | | 2(-6p+7)+4(p+3)= | | 3x^2-20x+25= | | 11d-4d-3d+d-4d=12 | | 23-4r=3 | | -48-3x=42+2x | | 6X9-/5X | | (14-2x)+40= | | 3(6+t)-1= | | 3(-5x-4)-2x=6 | | 3a^2+4a-7= | | 5x+2(6x-18)=117 | | 5m+-2-7m=20 | | 4=36/m | | 3a-5=5+a | | -6=14n | | 18x-4(3x+4)=(9x-5)-5(3x+7) | | 15xy-30y= | | 3d-2d-d+2d=8 |

Equations solver categories